Mitotic recombination as evidence of alternative pathogenesis of gastrointestinal stromal tumours in neurofibromatosis type 1 - Stewart, Douglas R (BMJ Group, 2007)
BACKGROUND: Neurofibromatosis type 1 (NF1) is a neurocutaneous disorder resulting in the growth of a variety of tumours, and is inherited in an autosomal dominant pattern. Gastrointestinal stromal tumours (GISTs) are mesenchymal tumours that commonly harbour oncogenic mutations in KIT or PDGFRA and are thought to arise from the interstitial cells of Cajal (ICC; the pacemaker cells of the gut). AIM: To characterise two patients with NF1 and GISTs. METHODS: Two patients were genotyped for germline mutations in NF1. GISTs from both patients were genotyped for somatic mutations in KIT and PDGFRA. Loss of heterozygosity (LOH) of NF1 in one GIST was assessed by genotyping seven microsatellite markers spanning 2.39 Mb of the NF1 locus in the tumour and in genomic DNA. The known germline mutation in NF1 was confirmed in GIST DNA by sequencing. The copy number of the mutated NF1 allele was determined by multiplex ligand‐dependent probe amplification. RESULTS: GISTs from both patients were of wild type for mutations in KIT and PDGFRA. In the GIST with adequate DNA, all seven markers were informative and showed LOH at the NF1 locus; sequencing of NF1 from that GIST showed no wild‐type sequence, suggesting that it was lost in the tumour. Multiplex ligand‐dependent probe amplification analysis showed that two copies of all NF1 exons were present. CONCLUSIONS: This is the first evidence of mitotic recombination resulting in a reduction to homozygosity of a germline NF1 mutation in an NF1‐associated GIST. We hypothesise that the LOH of NF1 and lack of KIT and PDGFRA mutations are evidence of an alternative pathogenesis in NF1‐associated GISTs.